Penyadaran Pentingnya Kesehatan Melalui Senam Dan Kebersihan Lingkungan Di Lembaga Kesejahteraan Sosial Anak Budi Mulia Plosoklaten Kediri - Amilia Rahmahwati (LP3M IAIFA Kediri, 2022)
Health is a complete state of physical, mental, and social well-being and is not just about illness or infirmity. Health is one of the basic needs of the community, so health is a right for every citizen of the community protected by the Basic Law. The definition of Health according to wikipedia is a state of well-being of the body, soul, and social that allows everyone to live a socially and economically productive life. Cleanliness is a state of being free from dirt, including being free from dust, garbage, dirt, and unpleasant odors because dai is pseudo-alah including the process of transmitting infectious diseases caused by microbes, and harmful chemicals, the cleanliness referred to here also means being free from viruses. Environmental Cleanliness is the condition of a place that we live in every day such as a house, a place to work, and a place where many people gather. We must clean the cleanliness of the high school every day so that it is protected from infectious diseases and, viruses that can transmit diseases. Gymnastics is the main activity that is most beneficial in developing physical components and motor abilities.